Renovation versus New Construction and Building Decision Tool for Educational Facilities. (28th June 2016) - Pope, Carrie; Marks, Eric; Back, Edward; Leopard, Tim; Love, Thomas
Abstract : Renovation of an existing building is an accomplished stem of the construction industry because it supplies financial diversification for construction stakeholders. Although several construction planning tools and stakeholder alignment exercises have been developed, no tool exists to assist project owners to decide between renovating an existing building and new construction with a comprehensive decision criteria. The objective of this research is to create and test a renovation versus new building support decision tool for construction project stakeholders. The renovation versus new building support decision tool was created based on an extensive review of existing support tools and construction industry needs. The created tool was implemented to evaluate decisions of educational facilities by university officials experienced in project management. Results show the tool was effective in identifying relevant topics for discussion and guiding a group of stakeholders through an exercise in decision-making. Specifically, the tool was implemented by construction management personnel for university facilities currently under construction to evaluate the decision to renovate an existing building or new construction. The main contribution of this research is a framework and support decision tool readily implementable for construction project stakeholders desiring to determine if renovation or new construction is the optimal path for their specific objectives.